Pengaruh Pengetahuan Perpajakan, Sanksi Pajak, dan Insentif Pajak terhadap Kepatuhan Wajib Pajak PBB-P2 Kota Surabaya - Putri, Farshanda Shalihati; Akbar, Fajar Syaiful (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This reasearch intends to investigate the effects of taxation knowledge, tax penalties, and tax incentives on compliance with land and building taxes in Surabaya. The research methodology employed is quantitative in nature. The population under scrutiny consists of all taxpayers of PBB-P2 in Surabaya, totaling 645,140 individuals registered with the Surabaya City Regional Revenue Agency in 2024. Through probability sampling, specifically simple random sampling, a sample of 100 taxpayers was selected, with sample size intend to the Slovin. Data collected by through a questionnaire distributed to respondents, who are PBB-P2 taxpayers in Surabaya City. The questionnaire will be administered via an online platform using Google Form through social media channels, allowing respondents flexibility in providing their responses. The collected data underwent analysis using multiple regression analysis, processed using SPSS Version 29. The findings of the study reveal that taxion knowledge and tax penalties exert a significant impcat on compliance with land and building taxes, while tax incentives do not impact compliance with these taxes.